Child of St. Kilda - Waters, Beth. (Auburn, ME : Child's Play, 2019)
For over two thousand years, the inhabitants of St Kilda maintained a thriving, tightly-knit community on one of the most inhospitable places on Earth - ‘the island at the edge of the world’. Theirs was an isolated lifestyle completely dependent on the seasons and the elements for its survival. A lifestyle out of which developed a culture based on subsistence, resilience, mutual trust and caring. A culture that knew no crime, had no need of cash, and took care of its weakest members without question. This unique way of life came abruptly to an end in August 1930, when the now-depleted community of only thirty-six men, women and children begged the British Government to evacuate them to the mainland. Why did the islanders leave, and where did they go? What became of them? Told through the eyes of Norman John Gillies, one of the last children born on St Kilda, this is the remarkable story of a unique society and the harsh yet beautiful environment out of which it evolved.